Awareness of Doing 3M (Wearing Mask, Physical Distancing, Washing Hands) During Pandemic Era in Rural and Urban Families - Amira Dhisa Fakhira; Aditya Sukma Pawitra; Khuliyah Candraning Diyanah; Edza Aria Wikurendra; Imre Nagy; Nour Salah Mohammad Abdeljawad (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The spread of Covid19 could be prevented by breaking the chain of transmission through the practice of wearing a mask while going outside or being in a crowd, washing hands using hand soap under running water, and doing physical distancing (3M). The difference in information distribution and access about Covid19 between rural and urban citizens connected to the awareness of doing 3M. This research aims to analyze the correlation between awareness and practicing wearing masks, washing hands, and physical distancing within rural and urban citizens. Methods: Data was collected using mixed-method survey, was done both online and offline to reach respondents from several provinces in Indonesia. Data retrieval was done using a questionnaire, and there were 2,196 people participated as respondents. Results and Discussion: Logistic regression analysis showed that age (p = 0.042; OR = 1.117), sex (p = 0.000; OR = 0.377), living area (p = 0.000; OR = 2.291), and knowledge (p = 0,000; OR = 1,450) have the significant relation with respondents' awareness of doing 3M. The age group of 27-36 years old, female, and well-knowledged respondents has a higher awareness of doing 3M than other groups. Rural citizens with a good awareness of doing 3M (87.78%) are bigger than urban citizens (76.02%). Conclusion: The good awareness of rural citizens has shown that both area's citizens already had the equality of information access, especially about Covid19 prevention and the government's policy and programs to reduce the spread of Covid199